Implementation of a Simulation Model for Optimizing the Traffic Flow from Arafat to Muzdalifah - Jamjoom, Arwa (European Scientific Journal, ESJ, 2017)
This project simulates the flow of pilgrims when they travel from Arafat to Muzdalifah. The system includes the roads network that connects Arafat to Muzdalifah, which is represented as a queuing system with different queue measurements that simulate reality. The system also includes different types of transportation, such as small and large buses and trains, all of which are represented as objects with different size and colors. All system objects carry specifications as their corresponding source system objects, and these specifications are based on data collected by the Ministry of Hajj. The primary objective of the system is to answer â€œwhat ifâ€ questions to support decision making to optimize Hajj traffic, which can be achieved by manipulating the systemâ€™s variables and then by observing the key performance indicators of the system. The system presents the experimental results as visual feedback alongside written reports with statistics and illustrations.